Cold anammox process and reduced graphene oxide - Varieties of effects during long-term interaction. (1st June 2019) - Tomaszewski, Mariusz; Cema, Grzegorz; Ciesielski, Slawomir; Łukowiec, Dariusz; Ziembińska-Buczyńska, Aleksandra
Abstract: Because of its energy efficiency, the anaerobic ammonium oxidation (anammox) process has been recognized as the most promising biological nitrogen removal process, but its implementation in mainstream wastewater treatment plants is limited by its relatively high optimal temperature (30 °C). Recently, it was shown that during short-term batch experiments, reduced graphene oxide (RGO) displayed accelerated reaction activity at low temperatures (10–15 °C). In this study, the long-term effects of RGO on the low-temperature anammox process in a sequencing batch reactor (SBR), are studied for the first time, including different methods of interaction. The results presented here show that RGO can stimulate anammox activity up to 17% through two factors: bacterial growth stimulation, which was especially significant at higher temperatures (>15 °C), and an increase of the anammox reaction rate, which occurred only below 15 °C. The bacterial community structure was not influenced by addition of RGO. Moreover, after incubation in an anammox bioreactor, RGO showed signs of degradation and chemical changes as evidenced by the presence of oxygen and calcium on its surface. According to the literature and the obtained results, it is proposed that RGO is oxidized and oxygen is reduced by the organic mediator that is involved in the enzymatic reactions. However, activated sludge is a very complex structure created by numerous, undefined microorganisms, which makes it difficult to determine the exact oxidation mechanism. Graphical abstract: Image 10750 Highlights: Long-term effects of RGO on the low temperature anammox process was studied. Bacteria growth and reaction rate stimulation up to 15–17%. Degradation and oxidation of nanomaterial structure. No significant influence on microbial community.